Pola Kurikulum Yang Terstruktur Sebagai Dasar Misi Menurut Matius 28:19-20 Di Gereja Morning Star Indonesia - Kalauserang, Jimmy Piter; Baskoro, Paulus Kunto (Jurnal Teologi Berita Hidup, 2025)
The great commission is a command that must be carried out. The Great Commission is not an optional recommendation or suggestion. So carrying out the Great Commission is proof for every Christian that they make Jesus God. Failure to carry out the Great Commission is one of the factors inhibiting church growth and failure to fulfill the great command of the Lord Jesus. Therefore, the church needs to think about how to overcome any obstacles that arise in implementing the Great Commission, where many churches do not yet have a curriculum pattern for implementing the Great Commission. A structured curriculum pattern is needed in implementing the great commission in accordance with Matthew 28:19-20. This research method is a descriptive qualitative method. The aim of this research is first, to examine the mission pattern in Matthew 28:19-20. Second, create a mission curriculum pattern that can be implemented in the church. Third, implementing the curriculum pattern obtained from Matthew 28:19-20 in today's church.